Exploration of Bilingual Approach Implementation in Arabic Language Teaching during the International Teaching Internship Program in Thailand/Istiksyaf Tathbiq al-Madkhal Tsunaiya al-Lughah fi Ta’lim al-Lughah al-Arabiyah Khilala Barnamaj Mumarasat al-Dauliyah fi Thailand - Neneng Novita Aulia; Wanasmah Paduka; Dedih Wahyudin; Ade Arip Ardiansyah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
Teaching Arabic in an international context often faces complex communication challenges, especially in a double-foreign language environment where teachers and students do not share the same mother tongue. This study aims to explore the implementation of a bilingual approach, the integration of interactive digital media, and the application of cooperative methods in Arabic language learning in the International Field Experience Program (PPL) in Thailand. Using a descriptive qualitative approach with a case study method, data were collected through participatory observation, documentation, and interviews. Data analysis was conducted inductively through the stages of data reduction, data presentation, and conclusion drawing according to the Miles and Huberman model. The study's results show that using English as an instructional bridge serves as cognitive scaffolding, minimizing communication barriers. From the students' perspective, this approach provides added value by offering opportunities to master two foreign languages simultaneously, despite the limitations of the English vocabulary. The success of this process is supported by the synergy between interactive media and collaborative methods such as Teams Games Tournament (TGT), which can transform cognitive load into participatory learning activities. This study provides practical contributions to international practitioners in managing multilingual classrooms through adaptive, contextually grounded pedagogical strategies. غالباً ما يواجه تعليم اللغة العربية في السياق الدولي عقبات تواصل معقدة، لا سيما في بيئات "اللغة الأجنبية المزدوجة" (double-foreign language) حيث لا يتشارك المعلم والطلاب لغة أماً واحدة. تهدف هذه الدراسة إلى استكشاف تطبيق المنهج ثنائي اللغة، ودمج الوسائط الرقمية التفاعلية، وتطبيق أساليب التعلم التعاوني في تعليم اللغة العربية ضمن برنامج التدريب الميداني الدولي (PPL) في تايلاند. تعتمد الدراسة على المنهج الكيفي الوصفي مع أسلوب دراسة الحالة، حيث جُمعت البيانات من خلال الملاحظة بالمشاركة، والتوثيق، والمقابلات. كما تم تحليل البيانات استقرائياً عبر مراحل خفض البيانات، وعرضها، واستخلاص النتائج وفق نموذج "مايلز وهوبيرمان". وأظهرت النتائج أن استخدام اللغة الإنجليزية كجسر تعليمي يعمل كـ "سقالات معرفية" (scaffolding cognitive) تساهم في تقليل انقطاع التواصل. ومن وجهة نظر الطلاب، يوفر هذا المنهج قيمة مضافة تتمثل في فرصة إتقان لغتين أجنبيتين في آن واحد، رغم وجود تحديات تتعلق بمحدودية المفردات الإنجليزية المعقدة. وقد تعزز نجاح هذه العملية من خلال التآزر بين الوسائط التفاعلية والأساليب التعاونية مثل "مباريات الألعاب الجماعية" (TGT) التي نجحت في تحويل العبء المعرفي إلى أنشطة تعليمية تشاركية. تقدم هذه الدراسة مساهمة عملية للمتدربين الدوليين في إدارة الفصول الدراسية متعددة اللغات من خلال استراتيجيات تربوية تكيفية وسياقية.